Computer & Network Equipment Management System (CNEMAS) Application Measurement - Imelda Pangaribuan; A Rahman; S Mauluddin (Universitas Komputer Indonesia, 2020)
ABC is one of the state-owned enterprises in Indonesia. PT. ABC has policy to give some equipment for employees to rent. Application use to control all equipment that rent by employee named as CNEMAS (Computer & Network Equipment Management System Nasional). There are some problems faced by PT. ABC in using CNEMAS, such as accuracy and its roles at PT. ABC business process. Objective of this research is to measure maturity of CNEMAS. Method used in this research are structured approach method as analysis method and Information Technology Assurance Framework (ITAF) used as measurement method. Tools such as Flowcharts, Context Diagram and Data Flow Diagram used to describe the process in CNEMAS. The result of this research are gap found at AC2 (awareness and Communication Component) where the gap is 0.71. The conclusion is CNEMAS needs improvement in accuracy, equipment location, on time report production, and consistency.